Ziemiańskie gorzelnie w Królestwie Polskim w latach 1879–1913 - Puś, Wiesław (Zeszyty Wiejskie, 2016)
In the presented article the author has attempted to determine the involvement of the distilleries landowners in the industry distillery in Polish Kingdom. Well, even though distilleries landowners in the years 1879, 1900 and 1913 accounted for the vast majority of plants producing alcohol, focusing from 65.7% to 82.6% of the companies, however, in the manufacture of their participation after a growth of 53.3% in 1879 to 66.7% in 1900, it fell sharply in 1913 to 36.9%. These data indicate a rapid development of the industry distillery in the cities of the Polish Kingdom in the early twentieth century.